Review Article Biogas Development and Usage Current Perspectives and Opportunities, Future Outcomes and Prospects: Biogas Uses for Production of Renewable Energy (Biological Sciences - PJSIR, 2025)
Biogas production uses well-developed technology for the production of renewable energy and utilization of organic waste for monetary benefits all around the world specifically in third world countries. Biogas is produced by anaerobic digestion from microorganisms that follow different metabolic pathways so that organic matter may get decomposed. In recent times, this sector of renewable energy development has been growing rapidly since ancient times where households used it for power generation for many years. This review is a summary of the current trailblazing opportunities, future outcomes and prospects of what biogas development actually is and its retrospective throughout the years has also been viewed and summarized so that a fresher outlook can be given for better optimization of the process for utilizing this energy. This review also states how biogas can be utilized in third world countries for better energy generating outcomes.